FACTORS PARTICIPATIONG IN WASTE MANAGEMENT AFFECTION SOLID WASTE MANAGEMENT OF PEOPLE IN SUBDISTRICT ADMINISTRATIVE ORGANIZATIONS KHAI BOK WAN MUANG DISTRICT NONG KHAI PROVINCE - Noicharoen, Phunthila (Journal of MCU Nakhondhat, 2022)
The objectives of this research paper were 1) to study the level of participation, 2) to study the level of waste management, 3) to analyze the relationship between the factor participation variables affecting waste management, and 4) to study the recommendations on the availability of waste management. Participation in waste management of people in Khai Bok Wan Subdistrict Administrative Organization, Muang District, Nong Khai Province. It is a quantitative research. The sample group consisted of 351 people representing households. The sample size was calculated using Yamane's formula. The research instrument was a questionnaire. The statistics used in the research were frequency distribution, percentage, mean, standard deviation. Statistical hypothesis testing Pearson Product Moment Correlation and Multiple Regression Analysis by Enter method at the statistical significance level of .05. The results of the research were as follows: 1) The level of participation in waste management of people in Khai Bok Wan Subdistrict Administrative Organization. 2) The level of waste management of people in Khai Bok Wan Subdistrict Administrative Organization at a high level. 3) The results of an analysis of the relationship between the variables participating in waste management that affect the waste management of the people in the Khai Bok Wan Subdistrict Administrative Organization area overall were at a low level. 25.8% had an R2 = .258 and an F = 30.146 statistically significant at the .01 level, and 4) People's recommendations, namely, that garbage should be collected strictly in accordance with the time announced by the Sub-District Administrative Organization. and publicize the waste collection of Khai Bok Wan Subdistrict Administrative Organization